On the 'strudel and apples' theory of historiography: A reply to Chris Lorenz - Tucker, Aviezer (Historein, 2013)
Narrative philosophies of historiography and the positivist approach to the philosophy of historiography share an emphasis on analyzing the writings of historians, rather than their research and methods of inference, confirmation and justification. But neither approach to the philosophy of historiography asks the question about the relation of historiography with the evidence. There are no “facts” in historiography, distinct atomic units that need to be selected and then put together in the historian’s narrative workshop. Instead, the historian is searching for relevant evidence to infer from representations of the past that include explanations and causal relations. Since it is trivially true that all present phenomena are the effects of the past, the historian requires information theories that tell which present phenomena are likely to preserve which types of information about the past. The forging of a narrative is only the last stage in a long process of inference.